Desenvolvimento de revestimentos biopoliméricos de amido e de quitosana para grãos de café cru - Ferreira, Laura Fonseca (2017)
The storage of green coffee is an important item for coffee processing, given that, in this stage, the coffee must be preserved with all its quality characteristics until 1 year, guaranteeing a competitive stock in the interim harvest period. With this work, we aimed at developing polymeric coatings for green coffee as an alternative to prolonging the preservation of its quality. The experiment was divided into two stages. The first had the objective of finding the treatment that least modified that characteristics of water content and color of the raw coffee grains as well as the sensorial quality of the beverage. In this stage, starch and chitosan biopolymers were tested in pre-drying time in oven at 100oC of 1 or 3 hours, and number of immersions of the green coffee in the polymeric suspensions of 1 or 2. In the second stage, different ultrasonic agitation energies were used for incorporating α-tocopherol (TOC) in the polymeric suspensions, evaluating particle size and the polydispersity index (PDI) of these suspensions. The antioxidant action, hydrophobicity and surface energy were also evaluated in the films obtained from the polymeric suspensions. Posteriorly, water vapor permeability (WVP) and the mechanical characteristics of the chitosan films incorporated with α-tocopherol and bentonite clay (BNT) were evaluated. As a result of the first stage, the starch film with 3 hours of pre-drying and one immersion of the grains presented the best performance. Both biopolymers were adequate for application, given that they did not modify the sensorial characteristics of the beverage. The TOC polymeric suspensions with starch and chitosan presented average particle sizes of 255 nm and 462 nm, respectively, and presented good stability in relation to the PDI. The surface energies of the biopolymers presented no significant difference (p<0.05) between each other. The surface energy of the grains also presented no difference from the energy of the surface of the biopolymers, which indicated good interaction between the polymeric suspensions and coffee grain during the application of the coating. The treatment with the greatest antioxidant effect was the chitosan composite and TOC obtained with agitation energy of 960 J.mL-1, presenting 50.3% of antioxidant action. The incorporation of BNT to the selected film decreased WVP and the deformation at the puncture. We recommend the use of this treatment to coat green coffee by antioxidant activity and a lower water vapor permeability.